A prospective comparative study in the clinical outcome of trochanteric and subtrochanteric fracture femur with proximal femoral nail versus dynamic hip screw - Gowda, Pradyumna R.; J., Manjunath (International Journal of Research in Orthopaedics, 2017)
Background: Trochanteric fractures are the most common fractures encountered accounting for 50% of all hip fractures. Subtrochanteric femur fractures have high rate of complications associated with their management. 10%–34% of all hip fractures occur in the subtrochanteric region.The study was to compare the clinical outcome of trochanteric and subtrochanteric fracture femur with proximal femoral nail (PFN) versus dynamic hip screw (DHS). Methods: A prospective study of 50 patients with intertrochanteric and subtrochanteric fracture among which 30 were treated with Proximal Femoral Nail and 20 with Dynamic Hip Screw at SSIMS-SPARSH Davangere, Karnataka, India between June 2015 to November 2016. At final follow up results were assessed with Modified Harris Hip score. Results: Among the PFN Intertrochanteric fracture group, 9 patients showed excellent outcome, 6 patients showed good outcome and 2 patients showed fair outcome and 1 patient showed poor outcome. Among the PFN subtrochanteric fracture group, 7 patients showed excellent outcome, 3 patients showed good outcome and 1 patients showed fair outcome and 1 patient showed poor outcome. Among the DHS intertrochanteric fracture group, 3 patients showed excellent outcome, 3 patients showed good outcome and 2 patients showed fair outcome and 2 patient showed poor outcome. Among the DHS subtrochanteric fracture group, 1 patients showed excellent outcome, 2 patients showed good outcome and 3 patients showed fair outcome and 4 patient showed poor outcome. Conclusions: Fractures of the trochanteric region of the femur need a proper selection of implant based on fracture pattern. DHS has excellent results when used on stable fractures. For unstable fractures, PFN is the implant of choice. In case of subtrochanteric fractures PFN has better results in both stable and unstable fractures compared to DHS with less failure rates and restoring better hip biomechanics.